The Power of Partnership : Selected Speeches by Christine Lagarde, 2011-2019. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
A compilation of selected speeches by IMF Managing Director Christine Lagarde.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet